(untitled) (Jurnal iSpectrum, 2023)
With a gym or fitness center, people can do physical activities supported by complete equipment and training programs, making people more optimal in their training when exercising at the fitness center. In the development of the design of the Tropical Gym located in Badung, as a place for sports, it has become an attraction for tourists to carry out weight lifting activities and experience the unique sports atmosphere in the interior and equipment used by this gym, which uses wooden materials, giving this gym its own value. The existence of a gym that will be built in the Badung area is one of the business fields that is very prospective in the future and is in great demand in the business world. Gyms themselves can also be found in urban areas and have spread to rural areas. And the surrounding community responded positively when the gym appeared, prospective members were very selective in determining the choice of gym or fitness center to use for training. The gym provides sports classes such as boxing, yoga, stationary bicycles and there is a bar that serves healthy food and drinks high in protein. By exercising regularly and living a healthy lifestyle, your muscles will become stronger, healthier and free from disease, as well as fitter and more youthful. Therefore, an idea emerged to design this gym design.